1996
DOI: 10.1103/physrevb.53.5240
|View full text |Cite
|
Sign up to set email alerts
|

Raman scattering and the evolution of polar order in Li-doped and Nb-doped KTaO3

Abstract: A comparative study of first-order Raman scattering in K 0.984 Li 0.016 TaO 3 and KTa 0.976 Nb 0.024 O 3 single crystals has been performed. The soft-phonon line shows marked differences in the two systems, revealing a distinctive behavior with regard to the scale of polar order. Analysis of the low-frequency spectrum allows for an estimate of the polar correlation length in the Li-doped sample; this is limited to the nanometric scale, in agreement with the view of a dipole-glass transition. No evidence of a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
20
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 40 publications
(45 reference statements)
5
20
1
Order By: Relevance
“…This model had been suggested in [43] and supported by X-ray absorption fine structure experiments [44] and theoretical calculations [45 -49]. At the same time, this disagrees with experimental findings [9,21,36,50], where, for example, no simple relationship between first order Raman intensity and Nb concentration was found. Moreover, according to NMR study on 93 Nb [20,51], Nb 5þ impurities are on-centre at high temperatures, but freeze out in off-centre position below T C due to interaction with the soft mode.…”
Section: Introductioncontrasting
confidence: 70%
See 2 more Smart Citations
“…This model had been suggested in [43] and supported by X-ray absorption fine structure experiments [44] and theoretical calculations [45 -49]. At the same time, this disagrees with experimental findings [9,21,36,50], where, for example, no simple relationship between first order Raman intensity and Nb concentration was found. Moreover, according to NMR study on 93 Nb [20,51], Nb 5þ impurities are on-centre at high temperatures, but freeze out in off-centre position below T C due to interaction with the soft mode.…”
Section: Introductioncontrasting
confidence: 70%
“…The spectra were recorded with a resolution of 2 cm 21 at cooling run and after cooling the sample at a constant rate of 1 K/min from 100 K to the lowest attainable temperature (11 K) and subsequent heating to the temperature of measurement. The spectral regions inspected were 8 -120 and 520 -600 cm 21 , where the soft TO 1 and hard TO 4 modes can be observed, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in the past, on the two well-known quantum paraelectric systems, ST ͑Refs. 2-8, 17, and 18͒ and KTaO 3 , [19][20][21][22][23] have shown that ferroelectric correlations develop only at temperatures well below room temperature ͑300 K͒. In this scenario, unless something dramatic takes place, a ferroelectric state by chemical substitutions in quantum paraelectric systems is not expected to occur at high temperatures ͑near 300 K or above͒.…”
mentioning
confidence: 99%
“…27 In contrast, no electric field effect was reported in the TO 1 spectrum of KTN with x D 0.024. 28 This shows that the long-range order is achieved in this crystal, even in the spontaneous case. 28 As the cluster number is directly related to the Nb content, this means that the long-range order is more rapidly reached in KTN2.4% than in KTN1.2%.…”
Section: Raman Spectra Under An Electric Fieldmentioning
confidence: 80%